Checklist, new species and new records of Cerambycidae (Insecta: Coleoptera) from Chapada Diamantina, Bahia state, Brazil - Nascimento, Francisco E. De L.; Mermudes, José Ricardo M.; Bravo, Freddy; Santos-Silva, Antonio (Zootaxa, 2017)
A checklist of Cerambycidae from three Brazilian localities of the Chapada Diamantina mountain range (Catolés, Piatã and Mucugê) is provided. These three localities are considered of great biological importance. A total of 38 species were collected, belonging to 29 genera, 18 tribes and two subfamilies. Ten new records for the state of Bahia are presented, and a new species, Desmiphora (Desmiphora) iwasarai (Desmiphorini, Lamiinae), is described and illustrated.